CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING WORK-LIFE-BALANCE IN MSMEs: A QUALITATIVE STUDY AT RUMANGSA KOPI PONTIANAK - Aris Mudiansyah Mudiansyah; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study explores the opportunities and challenges of implementing Work-Life Balance (WLB) in the MSME sector, using a case study at Rumangsa Kopi Pontianak. Adopting a descriptive qualitative approach, data were collected through in-depth interviews and participatory observation of part-time employees, mostly university students. Findings reveal that flexible scheduling, a familial work culture, and open communication are key enablers of WLB. Nevertheless, challenges remain, such as the absence of written SOPs, uneven workload during peak hours, and limited rest facilities. This study affirms that WLB can be adaptively implemented in MSMEs through a humanistic approach and contributes to the development of more inclusive and contextual HRM practices.